“Youtube Go”: Developing EFL Learners’ Listening Skills and Social Learning Process - Yohannes Telaumbanua; Hendro Saptopramono; Yalmiadi Yalmiadi (ITScience (Information Technology and Science), 2022)
The sophisticated advance in digital technology, one of which is YouTube Go, has not specifically fully significantly affected the EFL learners’ English Listening enhancement and other required critical skills accompanying it. The fact is, to this day, YouTube has not yet become the most critical learning medium in the Listening Comprehension instructional program. Therefore, the study, whose paradigm employed qualitative research, aimed at diagnosing the benefits of taking YouTube Go as a major listening comprehension instructional resource. Personal journal, observation as a complete participant, and informal interviews were techniques for collecting the qualitative data. Organizing, interpreting, and conclusion drawing were ways of analyzing the data. Credibility and audibility were ensured to examine the data. The findings indicated that YouTube Go improves students’ linguistic inputs, vocabulary knowledge, productive skills, and debating skills. Besides, it develops the students’ appreciative, discriminative, comprehension, attentive, reflection, critical, evaluative, dialogic, relationship, empathetic, therapeutic, sympathetic listening skills. It also establishes the teacher-learners and students learners' social and interaction skills, learning skills, literacy skills, and life skills. It encourages teachers to assess the students’ knowledge and skills authentically. In conclusion, YouTube Go extensively enhances the students’ language skills, listening skills, social skills, and social learning process.